Impacts of Customer Relationship Management (CRM) on Development of Corporations - Moser Martin (2021)
In markets with highly competitive pressure, like in the packaging industry, companies can only secure their existence by building and assuring long-term competitive advantages via the use of Customer Relationship Management (CRM). The primary goal of CRM is an increase of the corporate value via higher customer satisfaction. One indispensable success factor is the acceptance by its users. The identification of design features of CRM-systems, which have a positive influence on the development and profit of corporations in the packaging industry, would mean a crucial competitive advantage and enable the specifically orientation of the CRM-system on this benefit. This topic has not been discussed so far in the literature for the packaging industry. The lack of empirical contributions to measure the success of CRM-systems contrasts with the great interest in practice and encourages the desire to close this gap. The overall goal of this doctoral thesis is the identification of design features and prerequisites for a CRM-system, which contribute to an increase in sales and the overall development of corporations in the packaging industry. Particular attention is paid to the identification of requirements of a CRM-system that contribute to an increase in the acceptance of the users. The identified criteria can be used for further CRM-implementations to ensure a proper usage and approval, and furthermore the achievement and assurance of the intended purpose of a holistic CRM-approach. The theoretical part of this thesis is based on an extensive literature research. The case study has been chosen as the overall research design, which allows an intensive examination of the research material, whereby more extensive and complex results can be derived. The data collection of the qualitative research will be done by means of guideline-based and problem-centred interviews and the material will be analysed using the content analysis. A quantitative investigation via an online questionnaire is carried out afterwards to empirically check the developed hypotheses, derived from the qualitative research, via a statistics program. For a positive impact of CRM-systems on the profit and overall development of corporations in the packaging industry, many necessary requirements must be met first. It is important to consider possible problems in advance, and to avoid them accordingly. Only after the creation of these basic prerequisites or framework conditions, a CRM-system can unfold its intended and expected benefits, which positively influence acceptance, efficiency, and increase the profit.